INTENSI OWNER-MANAJER UMKM KABUPATEN SLEMAN MENGEMBANGKAN BISNIS RAMAH LINGKUNGAN - Suko Rina Adibatunabillah; Heru Kurnianto Tjahjono; Meika Kurnia Puji Rahayu DA (UIN Sunan Kalijaga, 2022)
Environmentally friendly trends are currently gaining global attention, including environmentally friendly businesses that play an important role in business sustainability. MSMEs are one of them, and they play a role in reducing negative environmental consequences on business operations. However, the goal of this study is to provide a broader viewpoint in understanding the owner- desire manager's to establish an environmentally friendly business based on the theory of planned behavior, specifically about the intention of the MSME owner- manager to develop an ecologically friendly business in their business. This research is a quantitative study with the research subject is the owner-manager of SMEs in Sleman Regency as many as 136 respondents with characteristics; owner-manager of MSMEs registered with the Cooperatives and SMEs Office of Sleman Regency, MSMEs are one of the MSME business sectors that are still actively operating today and are recommended by the Sleman Regency Cooperatives and SMEs Office. The primary data source is a questionnaire, which consists of 34 statement items, and is measured using a 5-point Likert scale. The data analysis technique uses Structural Equation Modeling (SEM) with the help of the Smart-PLS application. Theoretically, the analysis results show that attitude has a positive effect on environmentally friendly business intentions with a significance value of P-Value 0.001 and t-statistical 3.308; subjective norm has a positive effect on environmentally friendly business intentions with a significance value of P-Value 0.002 and t-statistical 3.162; and perceived behavioral control on environmentally friendly business intentions, the significance value of P- Value is 0.007 and t-statistic is 2.718. Empirically, this study reveals the owner-manager's intention to develop an environmentally friendly business, such as the environmentally friendly attitude of the MSME owner- manager, the support from the people closest to him to develop an environmentally friendly business in MSMEs, as well as perceived behavioral control which includes the knowledge and mastery possessed. MSME owner- managers for their abilities and resources needed to achieve environmentally friendly business intentions.